1997
DOI: 10.1124/mol.52.3.535
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Src Kinase in the Potentiation by Ethanol of Cytokine- and Endotoxin-Mediated Nitric Oxide Synthase Expression in Rat Hepatocytes

Abstract: This study demonstrates that exposure of primary rat hepatocytes or mouse BNL Cl.2 liver cell line to ethanol causes potentiation of tumor necrosis factor-alpha (TNF-alpha)- and lipopolysaccharide (LPS)-stimulated nitrite accumulation. The potentiating effect of ethanol (0.02-2 mM) appears to be time and concentration dependent. Consistent with nitrite production, the amount of inducible nitric oxide synthase (iNOS) mRNA and protein is initially detected at 4 hr after treatment with TNF-alpha/LPS/ethanol. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…40 Discrepant findings with different protein tyrosine kinase inhibitors as shown here for genistein and herbimycin A were also recently described for the regulation of inducible nitric oxide synthase mRNA in primary rat hepatocytes, 30 suggesting different target proteins for each inhibitor. However, exactly where genistein and herbimycin A interfere with the 2 separate PAI-1 inductory pathways for PMA and IL-␣ is not clear at present and requires further research.…”
Section: 39mentioning
confidence: 71%
See 1 more Smart Citation
“…40 Discrepant findings with different protein tyrosine kinase inhibitors as shown here for genistein and herbimycin A were also recently described for the regulation of inducible nitric oxide synthase mRNA in primary rat hepatocytes, 30 suggesting different target proteins for each inhibitor. However, exactly where genistein and herbimycin A interfere with the 2 separate PAI-1 inductory pathways for PMA and IL-␣ is not clear at present and requires further research.…”
Section: 39mentioning
confidence: 71%
“…First, we examined the effect of another protein tyrosine kinase inhibitor, herbimycin A. Herbimycin A, like genistein, was previously demonstrated to block IL-1␣-stimulated PAI-1 gene expression in cultured human endothelial cells, 20 but different target proteins have been suggested for each inhibitor. 30 As shown in Figure 4, herbimycin A (0.3 g/mL) potently inhibited IL-1␣-induced PAI-1 mRNA expression, but unlike genistein, was ineffective toward PMA-stimulated PAI-1 and CAT mRNA induction. Also in contrast to genistein, herbimycin A had no effect on c-jun or c-fos mRNA induced by IL-1␣ or PMA (data not shown).…”
Section: Effect Of Herbimycin a Ro 31-8220 Pd98059 And Sb 203580 Omentioning
confidence: 81%
“…The PTK p59 fyn is a possible target for these inhibitors, because it was shown to be involved in NF-B-mediated activation of the HIV long terminal repeat promoter (31). Discrepant findings with different PTK inhibitors as shown here for genistein and herbimycin A were recently described for the regulation of inducible nitric-oxide synthase mRNA in primary rat hepatocytes involving the PTK pp60 c-src (25), suggesting different target proteins for each inhibitor.…”
Section: Inhibition Of Cytokine-induced Nf-b Transactivation 6608mentioning
confidence: 90%
“…24 However, NAC failed to inhibit iNOS induction in rat hepatocytes. 26 In hepatocytes, intracellular glutathione was reported to be required for cytokine-induced NF-B activation and iNOS expression because the iNOS induction was prevented by glutathione depletion and could be restored by addition of NAC. 27,28 The results from the present study showed no obvious effect of NAC on cytokine activation of NF-B, which was consistent with previous reports 29 that indicated no inhibitory effect of NAC on IL-1-and TNF-activated NF-B in some cell lines.…”
Section: Discussionmentioning
confidence: 99%